Gas-phase interstitial modification of rare-earth intermetallics. - COEY, JOHN MICHAEL DAVID (IEEE, 1992)
The gas-phase interstitial modification of rare-earth intermetallics is studied. Net reaction energies for nitrogen in Sm2Fe17 and Nd(Fe11Tl) are U 0=-57 kJ/mole and U0=-51 kJ/mole, respectively. The equilibrium nitrogen concentration is calculated as function of temperature and gas pressure using a simple lattice gas model. For nitrogen in Sm2Fe17, refined diffusion parameters D0(N)=1.02 mm2/s and Ea(N)=133 kJ/mole, determined by thermoplexic analysis of the initial stage of nitrogen absorption, are used to calculate nitrogen profiles and the time dependence of the mean nitrogen content during nitrogenation. Similar values are obtained for nitrogen in Nd(Fe11Tl), whereas the activation energies for hydrogen in Sm2Fe17 and Nd(Fe11Tl) are 31 kJ/mole and 45 kJ/mole, respectively. The elastic stress and strain profiles during nitrogenation are calculated. Important results are a large uniaxial strain near the surface of nonuniformly nitrided particles, and core expansion even in the absence of any nitrogen there
PUBLISHED
Keywords: Physics